Feasibility of laparoscopic enucleation for hemangioma in special hepatic segments - Li, Huixing; Duan, Xuhong; Wu, Zhenyu; Qin, Yugang (Frontiers in Surgery, 2023)
Background and aim This study aims to evaluate the safety and efficacy of laparoscopic enucleation for liver hemangioma in special hepatic segments. Methods We retrospectively reviewed 58 patients who underwent laparoscopic surgery for hepatic hemangioma at a single center from January 2016 to January 2022. Segments I, IVa, VII, and VIII are defined as special hepatic segments, attributing to the bad visualization and adjacent to important vessels such as hepatic veins and inferior vena cava that lead to a high risk in laparoscopic surgery. Patients were categorized into a special location group (SLG) and a normal location group (NLG) according to the location of hemangioma. General data, intraoperative and postoperative outcomes, and postoperative complications of the two groups were compared and analyzed. Results There were no significant differences in age (p = 0.288), gender (p = 0.331), body mass index (p = 0.168), the maximum diameter of hemangioma (p = 0.330), ASA risk grading (p = 0.615), and comorbidities (p > 0.05) between the two groups. The operation time (p < 0.001), intraoperative blood loss (p < 0.001), and intraoperative blood transfusion rate (p = 0.047) were significantly higher in the SLG. The rate of conversion to laparotomy was higher in the SLG, but there was no significant difference (p = 0.089). In addition, the exhaust time (p = 0.03) and postoperative hospital stay (p < 0.01) were significantly shorter in the NLG. The postoperative complications were comparable between the two groups, and there were no perioperative deaths. Conclusion Laparoscopic enucleation of hemangioma in special hepatic segments is difficult and has a critical risk of massive bleeding during surgery. Meanwhile, it is also safe, feasible, and effective.